A Qualitative Study of the Real-world Experiences of Infectious Diseases Fellows Regarding Antibiotic Stewardship. (3rd May 2018) - Morgan, Jake R; Barlam, Tamar F; Drainoni, Mari-Lynn
Abstract: Background: Antibiotic-resistant bacterial infections are a major threat to public health, yet improper use of antibiotics remains high. Infectious Diseases (ID) fellows play a major role in antibiotic stewardship efforts, but there is little research on how they view stewardship activities. We performed a qualitative study to explore ID fellows' experiences and perspectives regarding their antibiotic stewardship training and their role as future antibiotic stewards. Methods: We conducted 17 in-depth interviews with ID fellows across the country. The interviews were transcribed verbatim by the study team, and we used grounded theory to generate themes from these interviews Results: Fellows focused on concrete tasks of stewardship such as performing antibiotic approvals, didactic and case-based education, and interactions with other physicians and pharmacists. There was little focus on the broader public health relevance of antibiotic stewardship. Pharmacists, not ID physician leaders, were identified as fellows' primary resource for antibiotic teaching. Several fellows suggested that stewardship programs should be led by pharmacists. Conclusions: ID fellowship training is not successfully conveying the public health importance of antibiotic stewardship or the role of ID physicians as leaders of antibiotic stewardship programs. Fellows are more focused on concrete tasks related to stewardship. ID training programs and societies should consider developing robust curricula involving fellows in the operation of the stewardship program itself, not solely in antibiotic approvals, emphasizing aspects of the program such as complex problem solving that fellows find most compelling, and emphasizing the important role these programs serve in improving public health.